Merging functional and structural properties of the monkey auditory cortex - Joly, Olivier; Baumann, Simon; Balezeau, Fabien; Thiele, Alexander; Griffiths, Timothy D. (Frontiers in Neuroscience, 2014)
Recent neuroimaging studies in primates aim to define the functional properties of auditory cortical areas, especially areas beyond A1, in order to further our understanding of the auditory cortical organization. Precise mapping of functional magnetic resonance imaging (fMRI) results and interpretation of their localizations among all the small auditory subfields remains challenging. To facilitate this mapping, we combined here information from cortical folding, micro-anatomy, surface-based atlas and tonotopic mapping. We used for the first time, phase-encoded fMRI design for mapping the monkey tonotopic organization. From posterior to anterior, we found a high-low-high progression of frequency preference on the superior temporal plane. We show a faithful representation of the fMRI results on a locally flattened surface of the superior temporal plane. In a tentative scheme to delineate core versus belt regions which share similar tonotopic organizations we used the ratio of T1-weighted and T2-weighted MR images as a measure of cortical myelination. Our results, presented along a co-registered surface-based atlas, can be interpreted in terms of a current model of the monkey auditory cortex.